Kajian biosintesis dan akumulasi beta-karoten pada tanaman makanan ternak serta implikasinya terhadap kualitas nutrisi hijauan - Syafiradewi Yulianti; Mansyur; Iin Susilawati (Fakultas Pertanian Universitas Majalengka, 2026)
Beta-carotene is the primary provitamin A carotenoid and natural antioxidant in forage plants, yet its biosynthesis and accumulation in tropical forages remain insufficiently characterised. This review systematically examined the biosynthetic pathways, regulatory factors, and nutritional implications of beta-carotene in forage plants using 45 peer-reviewed articles selected through a PRISMA-adapted protocol. Beta-carotene biosynthesis proceeds via the plastidial MEP pathway, with phytoene synthase (PSY) and lycopene beta-cyclase (LCYB) as principal regulatory enzymes. Accumulation varies substantially across forage species and is governed by harvest age, light intensity, temperature, and post-harvest management, with silage conserving up to 75–85% of initial beta-carotene content compared with losses of 70–90% during hay-making. In ruminants, an estimated 20–70% of ingested beta-carotene survives ruminal degradation (Wyss, 2020; Nozière et al., 2021; Calderón et al., 2020) and is subsequently absorbed and converted to vitamin A, supporting reproductive performance, immune function, and milk quality. Tropical legumes such as Leucaena leucocephala and Stylosanthes guianensis are rich beta-carotene sources, whereas data for Indonesian-specific cultivars of Napier grass, gamal (Gliricidia sepium), and indigofera (Indigofera zollingeriana) remain scarce. Strategic forage selection, optimised harvest intervals, and targeted supplementation are recommended to maximise beta-carotene delivery to ruminants under tropical conditions.